Successful direct acting antiviral (DAA) treatment of HCV/HIV-coinfected patients before and after liver transplantation - Grottenthaler, Julia; Stremmel, Wolfgang; Pathil-Warth, Anita (PLOS ONE, 2018)
Objectives: The aim of this multicenter retrospective study was to investigate safety and efficacy of direct acting antiviral (DAA) treatment in the rare subgroup of patients with HCV/HIV-coinfection and advanced liver cirrhosis on the liver transplant waiting list or after liver transplantation, respectively. Methods: When contacting 54 German liver centers (including all 23 German liver transplant centers), 12 HCV/HIV-coinfected patients on antiretroviral combination therapy were reported having received additional DAA therapy while being on the waiting list for liver transplantation (patient characteristics: Child-Pugh A (n = 6), B (n = 5), C (n = 1); MELD range 7-21; HCC (n = 2); HCV genotype 1a (n = 8), 1b (n = 2), 4 (n = 2)). Furthermore, 2 HCV/HIV-coinfected patients were denoted having received DAA therapy after liver transplantation (characteristics: HCV genotype 1a (n = 1), 4 (n = 1)). Results Applied DAA regimens were SOF/DAC (n = 7), SOF/LDV/RBV (n = 3), SOF/RBV (n = 3), PTV/r/OBV/DSV (n = 1), or PTV/r/OBV/DSV/RBV (n = 1), respectively. All patients achieved SVR 12, in the end. In one patient, HCV relapse occurred after 24 weeks of SOF/DAC therapy; subsequent treatment with 12 weeks PTV/r/OBV/DSV achieved SVR 12. One patient underwent liver transplantation while on DAA treatment. Analysis of liver function revealed either stable parameters or even significant improvement during DAA therapy and in follow-up. MELD scores were found to improve in 9/13 therapies in patients on the waiting list for liver transplantation; in only 2 patients a moderate increase of MELD scores persisted at the end of follow-up. Conclusion: DAA treatment was safe and highly effective in this nation-wide cohort of patients with HCV/HIV-coinfection awaiting liver transplantation or being transplanted.
Gesehen am 20.05.2019